High‐Efficiency Cryo‐Thermocells Assembled with Anisotropic Holey Graphene Aerogel Electrodes and a Eutectic Redox Electrolyte. Issue 25 (29th April 2019) - Li, Guangyong; Dong, Dapeng; Hong, Guo; Yan, Lifeng; Zhang, Xuetong; Song, Wenhui
Abstract: Thermocells, capable of converting temperature‐dependent electrochemical redox potentials into electrical power, can harvest waste or low‐grade heat in an economical and continuous approach with zero carbon emission. However, the power density and conversion efficiency of thermocells are hindered by a narrow operation window and low ion conductivity of the electrodes, especially in freezing weather conditions. Herein, highly efficient cylindrical thermocells, working in a wide operation window of cold temperatures, are developed. A eutectic electrolyte consisting of formamide and water is formulated with a high ion conductivity, which is retained at a significantly extended lower limit of the operation window from conventional 0 to −40 °C. In parallel, an electrode material based on anisotropic holey graphene aerogel is synthesized with improved ion conductivity, especially at temperatures below 0 °C, due to its aligned graphene sheets and pores. By taking the advantages of both components, the power density and the Seebeck coefficient of a single‐cylinder thermocell reaches an exceptionally high value, i.e., 3.6 W m −2 and 1.3 mV K −1, respectively. Moreover, assembled thermocells in series packaging substantially enhance the voltage of the open‐circuit, i.e., from 140 mV (1‐cylinder thermocell) to 2.1 V (15‐cylinder thermocells). Abstract : Highly efficient cylindrical cryo‐thermocells, working in a wide operation window of cold temperatures, are developed via the combination of anisotropic holey graphene aerogel electrodes and a eutectic redox electrolyte.